Recording and Audit of Resource Saving Innovations at Modern Industrial Companies - Mayorova, I. M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Resource saving and energy saving are essential components of “energy security” problem in all the countries, which raises the importance of analysis and revision of approaches to organization of recording and audit of resource saving innovations at industrial companies. The article’s objective is to study organization of recording and audit of resource saving technologies at industrial companies. A review of resource saving purposes and methods is given. For accounting purposes, innovations in resource saving are recorded now as intangible assets. Recording of resource saving innovations and technologies at industrial companies is confined to recording of transactions on creation or acquisition of patent rights objects and intellectual property objects. The author’s approach to organization of audit by the conformity of resource saving innovations with M. Porter’s test is proposed. Data showing success story of a Ukrainian company manufacturing polyurethane foam sealant PENADO in the aerosol dispenser is used to confirm that Ukraine does have potentials to introduce and utilize resource saving technologies, including energy saving ones. The proposed model for recording and audit of resource saving innovations should be used in strategic planning of resource saving innovations at the companies incorporated in industrial groups or holdings. Using this model, a company can reveal and assess the mismatch between amounts of resources that can be allocated in innovation and real capacities for introducing innovative resource saving technologies, and factors having the strongest impact on recourse saving innovations at companies incorporated in one financial and industrial group or holding. The proposed model accounts for the specific operative conditions in holdings and tough conditions for business operation of industrial companies in Ukraine.